Monolithic growth of GaAs/Al0.3Ga0.7As multiple quantum well structure on Ge substrate with low defects: theoretical and experimental correlation of the structural and optical properties. (31st July 2020) - Kumar, Ravinder; Panda, Debiprasad; Saha, Jhuma; Tongbram, Binita; Das, Debabrata; Kumar, Raman; Chakrabarti, Subhananda
Abstract: High quality III–V multiple quantum well (MQW) heterostructure on germanium (Ge) substrate is grown by molecular beam epitaxy. The propagation of defects and dislocations from the Ge/GaAs interface towards the active layer is suppressed via the adapted novel growth strategy. The cross-sectional transmission electron microscopy images showed the active layer of the MQW structure with reduced anti-phase domains and dislocations due to the introduction of migration enhanced epitaxy (MEE) and three-step annealed GaAs buffer layer. The optical properties are compared with another sample having similar heterostructure on GaAs substrate. The variation in full width half maxima with the well thickness has been analyzed via the correlation between photoluminescence (PL) result and calculated penetration depth of electron wave functions into the barrier material. The effect of substrate on the hetero-interface of MQW structure is also investigated. Rapid thermal annealing (RTA) is carried out on the sample with Ge substrate in order to explore the change in optical properties of the MQW structure. PL study indicates insignificant effect of low temperature RTA treatment on the thinner QWs. However, improvement in the optical property such as increment in activation energy and three order enhancement in the PL intensity was observed for the thicker QWs, owing to the amelioration in their structural property.